Awake videolaryngoscopic intubation in a pregnant patient with a large vocal cord lesion. Issue 2 (17th October 2016) - Thomas, Rajeev; McKnight, Angus; Athanassoglou, Vassilis
Summary: We describe the case of a 39‐year‐old female, 29 weeks pregnant who required urgent excision of a large laryngeal lesion. This was symptomatic, almost completely obstructing her glottis and creating a ball‐valve effect. Rapid progression of the lesion made the patient increasingly dyspnoeic and stridulous over the course of 2 weeks from presentation until surgery. Due to pregnancy‐related challenges and additional risks of complete airway obstruction, we conducted an awake videolaryngoscopic intubation supplemented with Transnasal Humidified Rapid‐Insufflation Ventilatory Exchange (THRIVE) for oxygenation. We discuss the anaesthetic challenges and management of this case, in particular this patient's airway pathology in the context of pregnancy. An overview of laryngeal pathology under the influence of pregnancy hormones is also presented.